Do firms make greater use of training and temporary employment when labor adjustment costs are high? - Gaëlle Pieree; Stefano Scarpetta (IZA Journal of Labor Policy, 2013)
In this paper, we present evidence on how employers in developing and emerging economies perceive employment regulations and react to them. We use harmonized surveys of about 10,800 firms around the world, supplemented by indicators of the stringency of employment protection that summarize detailed aspects of the labor legislation. We find that firms facing tight employment protection invest more in training, but also use temporary contracts to enhance labor flexibility. Using a difference-in-difference approach to control for unobservable characteristics, we find that small firms and those in sectors characterized by greater job reallocation are the most directly affected by employment protection.
Keywords: J23; J65; K31; 330; Employment protection indicators; Firm surveys; Training; Temporary employment